+0  
 
0
2612
1
avatar

Simplify the trigonometric expression  1 / 1 + sin Θ + 1 / 1 - sin Θ

 Apr 26, 2015

Best Answer 

 #1
avatar+126679 
+5

1 / [ 1 + sinΘ]  + 1 / [1 - sinΘ]  getiing a common denominator, we have

[1 - sinΘ + 1 + sinΘ ] / [ 1 - sin2Θ]  =

2/[1- sin2Θ] =

2/cos2Θ  =

2sec2Θ

 

  

 Apr 26, 2015
 #1
avatar+126679 
+5
Best Answer

1 / [ 1 + sinΘ]  + 1 / [1 - sinΘ]  getiing a common denominator, we have

[1 - sinΘ + 1 + sinΘ ] / [ 1 - sin2Θ]  =

2/[1- sin2Θ] =

2/cos2Θ  =

2sec2Θ

 

  

CPhill Apr 26, 2015

0 Online Users